Dakwah among Indian Mualaf in Malaysia - Razaleigh Muhamat @ Kawangit; Salawati Saringat (Penerbit Universiti Kebangsaan Malaysia, 2014)
This article sets out to look activities and challenges of dakwah among Indian Mualaf in Malaysia. It was sure that their Muslim culture applying becomes a dilemma when they are a Muslim minority group. It suggests that when this group begin to practice Islām, their behavior changes dramatically. This is because instead changing their faiths, they also need to maintain their new culture as Muslim converts. Whilst they are welcomed by their Indian Muslim counterparts, it is nevertheless hypothesized that they may not participate fully in the Muslim mainstream. This document research based method finally found that Indian Mualaf only involved with internal activities in order to build relationship between them and this given them a big challenge to put them as Muslim dominated by Malays in Malaysia.